Le bi-plurilinguisme : quand la représentation fait émerger les langues maternelles - Abdelnour Benazzouz (Lengas)
The aim of this sociolinguistic study is to bring out the representations of an ordinary Algerian speaker's bi- or plurilingual practice through the sociolinguistic interview. The latter points to bilingual practices in context according to levels of functioning that call for domains of use of alternation, which conveys a representation of languages rather than of bilingualism as a practice in its own right.